COMPARING THE EFFECTIVENESS OF STATIC AND DYNAMIC AUDIOVISUAL IN AN ADDITIONAL GEOGRAPHY LESSON IN ONE PATHWAY COLLEGE IN JAKARTA - Adelina, Erni; Hutabarat, Peny Meliaty (Jurnal Vokasi Indonesia, 2024)
Students are now used to using audiovisual platforms to learn as they once were forced to adapt to this type of learning due to face-to-face lessons were impossible at that time because of the pandemic. Audiovisual learning resources came out sporadically to accommodate the needs of study at home or anywhere possible. The static audiovisual (enhanced podcast) and dynamic audiovisual (video) are two types of virtual platforms educators continuously harness to support their lesson teachings even though the face-to-face meetings have been allowed gradually. However, there are not many studies conducted to analyze whether one type is more effective in teaching comprehension to students than the other. This paper is looking to find the answer. It questions if enhanced podcast with less complexity in their content pictures can actually become more practical for students to achieve comprehensions on teaching procedural or process topics in geography even it is less attractive than its counterpart, video. The study was conducted to five ESL students in an additional or extra geography class in Jakarta International College. The findings are: students saw enhanced podcasts or static audiovisual media (less complex picture contents) are giving them better learning experience than watching full-motion videos.